The Meaning Of “Fear Of Loss” In The Lyrics Of Lizzy McAlpine's Song “Staying” - Sayyidah Fitri Najiyah; Farida Nurfalah (Jurnal Polisci, 2026)
Background. This study analyzes the meaning of fear of loss in the lyrics of Lizzy McAlpine's song “Staying” using Roland Barthes' semiotic approach, which includes the levels of denotation, connotation, and myth. Aims. This study aims to reveal how fear of loss is described through song lyrics as media texts and how this meaning can be linked to the emotional experiences of listeners, especially the younger generation. Methods. The method used is descriptive qualitative research, with data collection techniques that include secondary and primary data, documentary studies of song lyrics supported by interviews, and validity tests through source triangulation. Result. The results of this study indicate that the lyrics of Lizzy McAlpine's song “Staying” describe the meaning of fear of loss through three levels of Roland Barthes' semiotics. At the denotative level, the lyrics describe a relationship that is still physically ongoing but accompanied by emotional exhaustion and doubt. Conclusion. At the connotative level, this song represents the fear of loss that drives the narrator to persevere and delay the breakup even though the relationship has become fragile. At the mythical level, the fear of loss is normalized so that remaining in a painful relationship is considered more acceptable than letting go. In addition, the interview results show that the meaning of the fear of loss in this song aligns with listeners' emotional experiences, in which the fear of loss drives individuals to delay separation and maintain closeness as a form of temporary security.